2022
DOI: 10.3390/medicina58010111
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Emergency Peripartum Hysterectomy in a Tertiary Obstetrics Unit in Romania

Abstract: Background and Objectives: Emergency peripartum hysterectomy (EPH) is a life-saving surgical procedure performed when medical and surgical conservative measures fail to control postpartum hemorrhage. The objective of this study was to estimate the incidence of EPH and to determine the factors leading to this procedure and the maternal outcomes. Materials and Methods: A retrospective cohort study with all cases of EPH performed at Filantropia Clinical Hospital in Bucharest between January 2012 and May 2021. Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
15
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 29 publications
2
15
0
Order By: Relevance
“…In the literature, the frequency of emergency obstetric hysterectomy varies from one region to another; indeed, if it has become exceptional in developed countries, it most often remains the last possible life-saving gesture for mothers in under-medicalized countries [2][3][4]. African studies have reported varying incidences: Sy T in Guinea (0.16%), Nayama in Niger (1.35%) and Abidi (1.3%) in Tunisia [5,6,7] while in developed countries the frequency is relatively low and varied between 0.52‰ to 1.07‰ of deliveries [8][9]. In developing countries, neglect or inaccessibility to prenatal care, ignorance of risk factors and danger signs of pregnancy, socio-economic factors and delays in early access to care expose women to often fatal hemorrhagic complications [2].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the literature, the frequency of emergency obstetric hysterectomy varies from one region to another; indeed, if it has become exceptional in developed countries, it most often remains the last possible life-saving gesture for mothers in under-medicalized countries [2][3][4]. African studies have reported varying incidences: Sy T in Guinea (0.16%), Nayama in Niger (1.35%) and Abidi (1.3%) in Tunisia [5,6,7] while in developed countries the frequency is relatively low and varied between 0.52‰ to 1.07‰ of deliveries [8][9]. In developing countries, neglect or inaccessibility to prenatal care, ignorance of risk factors and danger signs of pregnancy, socio-economic factors and delays in early access to care expose women to often fatal hemorrhagic complications [2].…”
Section: Discussionmentioning
confidence: 99%
“…This observation is made in our study with maximum obstetric hysterectomies in women in the age group of 30 to 34 years 33% (n = 33) and multiparas 72% (n = 72). Multiparity was found in many other African studies [5-10-11], in fact multiparity weakens the myometrium, thus favoring ruptures and uterine inertia [1][2][3][4][5][6][7][8][9][10][11][12]. Quality prenatal monitoring can detect certain factors early and take action (hypertension blood pressure in pregnancy, scarred uterus, surgical bedpans, and defective presentations) [13].…”
Section: Discussionmentioning
confidence: 99%
“…Although time‐trend analysis showed a decreasing tendency for the CS rate after 2017, it was still much higher than the WHO recommendations 13 . The CS rate and prior number of CS operations are strongly associated with the occurrence of AP 11,12,14 . Additionally, studies have shown that the risk of PH dramatically increases in pregnant women with complications of PP and or PAS and with prior cesarean deliveries 14–17 .…”
Section: Discussionmentioning
confidence: 99%
“…A question that needs to be answered when offering the option of EM when treating PAS is related to the risks of complications and need for a subsequent HT. Furthermore, women managed expectantly should be informed that they require long-term follow-up, with multiple hospital visits for blood tests and ultrasounds ( Figure 1 ) and immediate access to health care facilities [ 34 ].…”
Section: Discussionmentioning
confidence: 99%